2014
DOI: 10.1177/2168479013496245
|View full text |Cite
|
Sign up to set email alerts
|

A Data-Driven Approach to Risk-Based Source Data Verification

Abstract: Source data verification (SDV) is the process of confirming that reliable, accurate information collected from participants during a clinical trial has been reported successfully to the trial's sponsor by investigators conducting the study. Over the past 15 years or so, there has been considerable discussion in the literature of alternate (reduced and risk-based) approaches to the traditional 100% SDV approach, but these discussions have been theoretical rather than data driven. This research therefore employe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 13 publications
(36 reference statements)
0
12
0
Order By: Relevance
“…24 As a result, TransCelerate BioPharma has now developed a methodology that shifts monitoring processes from an excessive concentration on SDV to a more comprehensive risk-driven approach. 24 Lindblad et al 25 concluded that systematic central monitoring of clinical trial data can identify problems at the same trials and sites identified during FDA site inspections, and Nielsen et al 26 concluded that a “mixed approach” (ie, characterized by minimal amount of SDV) appeared to be most efficient.…”
Section: Introductionmentioning
confidence: 99%
“…24 As a result, TransCelerate BioPharma has now developed a methodology that shifts monitoring processes from an excessive concentration on SDV to a more comprehensive risk-driven approach. 24 Lindblad et al 25 concluded that systematic central monitoring of clinical trial data can identify problems at the same trials and sites identified during FDA site inspections, and Nielsen et al 26 concluded that a “mixed approach” (ie, characterized by minimal amount of SDV) appeared to be most efficient.…”
Section: Introductionmentioning
confidence: 99%
“…Other approaches that have been proposed are, for example, “targeted SDV” (ie, focus SDV on high-risk data points), “remote SDV” (allowing SDV to be performed centrally), or hybrid approaches. 1,4 –7,9 15 The TransCelerate Biopharma Inc guidance on risk-based monitoring estimated that, of all generated queries, the percentage generated through SDV is as low as 7.8% overall and 2.4% in critical data. 20 These numbers may suggest not performing SDV at all.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] Consequently, its use has been a major topic of debate in discussions on the efficiency of clinical trial monitoring, and various alternatives have been proposed. 1,[4][5][6][7][9][10][11][12][13][14][15] One alternative approach (which we term random SDV) is to limit SDV to a random sample of CRF entries: Inspection of a sample may be sufficient to assess the quality of all data provided by an investigational site. 1,[4][5][6][7]11 This view is supported by the Guidelines for Good Clinical Practice, which state that ''statistically controlled sampling may be an acceptable method for selecting the data to be verified.''…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For e.g. incorporation of centralized monitoring practices, where appropriate, should improve a sponsor's ability to ensure the quality of clinical trial data [1][2][3][4].…”
Section: Risk Based Monitoringmentioning
confidence: 99%